O uso do livro didático por professor e estudantes nas aulas de sociologia na Escola Estadual de Ensino Profissional Professor Francisco Aristóteles de Sousa em Itaitinga – Ceará - Santos, Alane Vale Farias dos (2021)
This work aims to investigate the way students and teacher of two second year high school classes, from the State School of Professional Education Professor Francisco Aristóteles de Sousa, located in the municipality of Itaitinga, Ceará, make use of the Sociology textbook, “Sociology in motion” by Afrânio Silva et al., In his learning process. Starting from the hypothesis that the uses of the textbook by the students go beyond the conditions set by the teacher in their classes, the work brings a field report of the observation of Sociology classes where the book is widely used. a brief summary of the reasons for the official documents that govern education in Brazil and the teaching of Sociology; how Sociology classes are elaborating at school; how students evaluate the textbook adopted by the school; a brief presentation of the thematic contents of the book and the proposal of an ideal lesson plan based on the curricular parameters and the textbook, suggesting an intersectional approach in Sociology classes. The methodology was participant observation, as the research is a product of the experience as a teacher in the researched school.